2001
DOI: 10.1016/s1573-5214(01)80019-1
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of a non-steady state rumen model

Abstract: The effects of the length of allowed grazing time (Experiment 1) and length of starvation period before grazing (Experiment 2) on dry-matter (DM) intake, ingestive behaviour and changes in DM rumen pool sizes during the first grazing bout were investigated in lactating Holstein-Friesian dairy cows. In Experiment 1, four lengths of allowed grazing time (1, 1·75, 2·50 and 3·25 h) after overnight starvation were compared. Increasing the length of the allowed grazing time significantly increased DM intake (P < 0·0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Although the simulation of a steady state within the rumen during continuous feeding has proved effective for the simulation of many aspects of rumen fermentation, the objectives of this investigation require pulsed model inputs, thus simulating rumen function in the cow fed a limited number of meals during the day. France et al (1982), Baldwin, (1995), and Chilibroste et al (2001Chilibroste et al ( , 2008 describe models of whole-rumen function for which inputs were either continuous or pulsed to represent discontinuous feeding schedules. Due to the objectives of the present model, the approach taken by France et al (1982) is used to simulate discontinuous feeding where instantaneous values for nutrient inputs (D x ) are represented as follows:…”
Section: Model Parameterizationmentioning
confidence: 99%
“…Although the simulation of a steady state within the rumen during continuous feeding has proved effective for the simulation of many aspects of rumen fermentation, the objectives of this investigation require pulsed model inputs, thus simulating rumen function in the cow fed a limited number of meals during the day. France et al (1982), Baldwin, (1995), and Chilibroste et al (2001Chilibroste et al ( , 2008 describe models of whole-rumen function for which inputs were either continuous or pulsed to represent discontinuous feeding schedules. Due to the objectives of the present model, the approach taken by France et al (1982) is used to simulate discontinuous feeding where instantaneous values for nutrient inputs (D x ) are represented as follows:…”
Section: Model Parameterizationmentioning
confidence: 99%
“…It is also possible that the equations developed for V ru are not applicable to these data for some reason, but this is difficult to determine without observed V ru values to compare against. An empirical representation of V ru was taken for this exercise, which allowed consideration of the RP% of the diet DMI and BW, but other approaches such as that of Chilibroste et al (2001) may be valid as well, where discontinuous feeding is represented and V ru is described mechanistically over time based on the DM% of rumen contents. As discontinuous feeding pattern data were not available for the independent beef database, an empirical approach was logical, although further investigation of whether the Chilibroste et al (2001) approach results in better predictions could be warranted.…”
Section: Ph Predictionsmentioning
confidence: 99%
“…The authors were satisfied that the model predictions were close to observed values and, based on simulations, recommended supplementing the basal diet with Leucaena and rice bran to increase milk production. Subsequently, Chilibroste et al (2001) and Rodrigues et al (2002) adapted the model to evaluate supplements to enhance the nutrient supply and milk production of cattle fed diets based on ryegrass and elephant grass, respectively. Behera et al (2005) also used the model to simulate milk production by dairy cows fed sugarcane top-based diets and other local supplements in India.…”
Section: Nutrient Utilization At the Animal And Whole-farm Levelsmentioning
confidence: 99%